Atividade amilolítica de extratos da germinação de milho e arroz - Borgo, Luiz Antônio; Teixeira Coelho, Dilson; Gomes, José Carlos; Kalagi Kibuuka, Godfrey (Revista Ceres, 2025)
Enzyme extracts with amylolytic activity capable of saccharifying soluble starch to fermentable sugars were obtained from corn and rice grains germinated for 7 days. The specific activities of the enzyme extract from corn proved to be more efficient than that obtained from rice.